Rantai Nilai Dan Ancaman Penyebaran Penyakit Baru Pada Agroinustri Pisang Di Pulau Flores Provinsi NTT - Nampa, I Wayan; Pudjiastuti, S.S.; Darlen , Maria Fransiska; Widinugraheni , Sri; Tay, Broni; Pero, Yoanita Elfini; Usman, Fauzi Ndewi Junior (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2025)
Banana is an important commodity to support farmers' household income, raw material for agro-industry. Any disruption to banana production will affect the income of farmers and industry players. Research is needed to determine the organization, contribution to income, and impact of the spread of Blood Desease bacteria (BDB) on the banana agro-industry. This study utilized a mixed methods approach that included both qualitative and quantitative components. Data was collected by conducting interviews with 151 farmer households, and key informants. The banana agro-industry involves various parties in on-farm, processing, trading and shipping services. Banana farming contributes 51%, or IDR 1,379,056/month to farm household income from the agricultural sector. Production costs incurred by farmers are very low, at only 5.5% of total revenue. The economic value of bananas in one month can reach Rp 1.4 billion/month (consumer level price) but of this value, the share received by farmers is only 30%, while the rest is marketing costs and profits in the marketing chain. The spread of BDB in some of the study locations caused a dramatic decline in production to the point where farmers did not produce any bananas. The new disease has also impacted the banana chip, fried banana, banana molen, and other banana processing industries, with raw material prices increasing by 50% to 200%. Therefore, managing the spread of the disease is very important not only for farmers, but also for all banana agro-industry players.